2010
DOI: 10.1364/ol.35.003691
|View full text |Cite
|
Sign up to set email alerts
|

Free-carrier absorption modulation in silicon nanocrystal slot waveguides

Abstract: Free-carrier absorption (FCA) has proven to be an important obstacle in the development of a silicon-based laser; however, FCA may serve as a potential advantage in active silicon-based switches or modulators. In this work, we present FCA modulation in slot waveguides with silicon nanocrystals (Si-ncs) embedded in SiO(2) as the low-index slot material. Slot waveguides were fabricated with and without Si-ncs, and the presence of Si-ncs was shown to increase the pump-induced FCA loss in the waveguides by a facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…Marchena et al demonstrated the FCA induced loss in the Si-QD based micro-disk at resonant frequency by optical pumping [23]. With the FCA effect in Si-QD doped SiO x waveguide modulator, the all-optical switching was performed by employing a pulsed pump laser to control the transient free-carrier density so as to rapidly modulate the probe signal passing through the Si-QD [24][25][26]. In principle, the FCA cross-section of the Si-QD can be affected by the QCE, such that the free carrier lifetime as well as the FCA modulation bandwidth can be manipulated by controlling the size of the Si-QD.…”
Section: Introductionmentioning
confidence: 99%
“…Marchena et al demonstrated the FCA induced loss in the Si-QD based micro-disk at resonant frequency by optical pumping [23]. With the FCA effect in Si-QD doped SiO x waveguide modulator, the all-optical switching was performed by employing a pulsed pump laser to control the transient free-carrier density so as to rapidly modulate the probe signal passing through the Si-QD [24][25][26]. In principle, the FCA cross-section of the Si-QD can be affected by the QCE, such that the free carrier lifetime as well as the FCA modulation bandwidth can be manipulated by controlling the size of the Si-QD.…”
Section: Introductionmentioning
confidence: 99%
“…Versatile passive and functional devices including couplers, multiplexers and demultiplexers, resonators, filters, and modulators have been emerged to meet the demands of the next-generation photonic integrated circuits. To fabricate a Si-based modulator with high modulation depth, several kinds of Si-based micro-or nano-structures, including rib/slot waveguide [1][2][3][4][5], nano-wire [6][7][8] and ring-resonator [9] were developed with mature fabrication technology in current Si industry. Recently, Si quantum dot (Si-QD) has been studied in several applications of silicon photonics, such as light emitting diodes (LEDs), distributed Bragg reflectors, waveguide amplifiers, modulator and switch, etc.…”
Section: Introductionmentioning
confidence: 99%
“…However, the optical gain of Si-QDs is still lower than that of III-V compound semiconductor materials, which results from the gain saturation effect of the Si-QDs [26][27][28]. More recently, free-carrier absorption (FCA) of the Si-QDs has also been investigated [1,3]. In 2009, Kekatpure et al have shown that the FCA cross-section in Si-QDs is one-order of magnitude larger than that in bulk Si [28].…”
Section: Introductionmentioning
confidence: 99%
“…Plasma waves can be detected by the measurement of the periodical component of the intensity of the IR radiation of the samples, in a PTR method, or by the measurement of the intensity of the periodical component of the transmitted probing IR beam of light in a MFCA method, or by the periodical photoluminescence in a photocarrier radiometry (PCR) method [1][2][3]. Analysis of the frequency characteristics enables determination of the recombination parameters of semiconductors with the PTR method [4,5] and the MFCA method [6][7][8][9][10][11][12]. For one layer samples, it is possible to determine the lifetime of carriers and the velocity of the surface recombination from the frequency amplitude and phase PTR or MFCA characteristics.…”
Section: Introductionmentioning
confidence: 99%